2017
DOI: 10.3390/ijms18102111
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 in Carcinomas and PARP1 Inhibitors as Antineoplastic Drugs

Abstract: Poly (ADP-ribose) polymerase 1 (PARP1), the best-studied isoform of the nuclear enzyme PARP family, plays a pivotal role in cellular biological processes, such as DNA repair, gene transcription, and so on. PARP1 has been found to be overexpressed in various carcinomas. These all indicate the clinical potential of PARP1 as a therapeutic target of human malignancies. Additionally, multiple preclinical research studies and clinical trials demonstrate that inhibition of PARP1 can repress tumor growth and metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 103 publications
(132 reference statements)
1
38
0
Order By: Relevance
“…In fact, evidence that supports both a tumor promoter and suppressor function of SIRT1 has been reported for TNBC and luminal breast cancer subtypes [142]. Concerning PARP1, its up-regulation has been reported in multiple cancers, while its inhibition has the capacity to suppress angiogenesis, metastasis, and tumor-induced inflammation [48].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In fact, evidence that supports both a tumor promoter and suppressor function of SIRT1 has been reported for TNBC and luminal breast cancer subtypes [142]. Concerning PARP1, its up-regulation has been reported in multiple cancers, while its inhibition has the capacity to suppress angiogenesis, metastasis, and tumor-induced inflammation [48].…”
Section: Discussionmentioning
confidence: 98%
“…As previously mentioned, NAM increases the levels of NAD + , boosts energy metabolism and protects cells from oxidative stress [39]. NAM also inhibits SIRT1 and PARP1, both of which have been shown to be up-regulated in multiple cancers [39,48,[137][138][139]. However, while it suppresses Despite the aforementioned evidence, more studies are needed to unravel NAM's entire molecular mechanism in diverse cancer scenarios, before its widespread implementation into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports have shown that PARP1 is over expressed in solid cancerous tissues . Integrating the in vitro and in silico results there is a possibility of PARP1 inhibition mediated cancer cell death .…”
Section: Resultsmentioning
confidence: 90%
“…In addition to malignant tissues of BRCA-mutant, triple-negative, and receptor-positive breast carcinoma, PARP1 is overexpressed significantly in uterine carcinoma and ovarian carcinoma. As in breast carcinoma, ovarian cancer cells show high sensitivity to drugs designed for PARP1 inhibition (Iqbal et al, 2012;Thompson & Easton, 2003;L. Wang et al, 2017).…”
Section: Ovarian Cancer and Breast Cancermentioning
confidence: 99%